Excellence in women’s health integrating menopausal medicine into Obstetric and Gynecology Residency Training Program - Maylem, Lornalyn C.
There are many challenges to the menopause stage of women. This must be major public health concern today. The POGS and PSCM understand the situation hence the requirement of every accredited medical institution to set up a menopause clinic. The Department of Health should also start making policies specifically for the menopausal women and not just the senor population in general. The physical requirements must be followed. The training program for the obstetrics and Gynecology must be implemented. The Instructional design for the menopause training has been made by the author to give life and spirit for the training. The author would like to recommend that research made on all patients of the Philippine menopausal clinics to check if all the outcomes of the program are effective in solving the problems of menopause.